Clinical usefulness of NGS multi-gene panel testing in hereditary cancer analysis - Anaclerio, Federico; Pilenzi, Lucrezia; Dell’Elice, Anastasia; Ferrante, Rossella; Grossi, Simona; Ferlito, Luca Maria; Marinelli, Camilla; Gildetti, Simona; Calabrese, Giuseppe; Stuppia, Liborio; Antonucci, Ivana (Frontiers in Genetics, 2023)
A considerable number of families with pedigrees suggestive of a Mendelian form of Breast Cancer (BC), Ovarian Cancer (OC) or Pancreatic Cancer (PC) do not show detectable BRCA1/2 mutations after genetic testing. The use of multi-gene hereditary cancer panels increases the possibility to identify individuals with cancer predisposing gene variants. Our study was aimed to evaluate the increase in the detection rate of pathogenic mutations in BC, OC and PC patients when using a multi-gene panel. 546 patients affected by BC (423), PC (64) or OC (59) entered the study from January 2020 to December 2021. For BC patients, inclusion criteria were (i) positive cancer family background, (ii) early onset and (iii) triple negative BC. PC patients were enrolled when affected by metastatic cancer, while OC patients were all submitted to genetic testing without selection. The patients were tested using a Next-Generation Sequencing (NGS) panel containing 25 genes in addition to BRCA1/2. Forty-four out of 546 patients (8%) carried germline pathogenic/likely pathogenic variants (PV/LPV) on BRCA1/2 genes, and 46 (8%) presented PV or LPV in other susceptibility genes. Our findings demonstrate the utility of expanded panel testing in patients with suspected hereditary cancer syndromes, since this approach increased the mutation detection rate of 15% in PC, 8% in BC and 5% in OC cases. In absence of multi-gene panel analysis, a considerable percentage of mutations would have been lost.